Global Governance in the 21st Century: A Digital Trends and Transformation - Alfarizi, Baqi Zaenulhaq; silvyasari, Deasy; Heryadi, Dudy (Global Local Interactions: Journal of International Relations, 2024)
This article explores the dynamics of global governance in the 21st century, focusing on the trends and digital transformations that are reshaping traditional paradigms. With technological advancements, global governance not only faces new complexities but also unprecedented opportunities for innovation. This research discusses the impact of digital transformation on global decision-making, the role of non-governmental actors, and the necessary adaptations to confront the digital era. Policy analysis highlights challenges in cybersecurity, the need for responsive regulations, and the involvement of non-governmental actors in shaping the direction of global policies. Considering the multilevel governance theoretical framework, this article examines how policy dynamics at the international, national, and local levels interact within the context of digital transformation. A profound understanding of the innovative roles of technology companies, non-governmental organizations, and civil society is central to explaining how global governance can be inclusive and empower all stakeholders. Flexibility in regulations, adaptation to cutting-edge technologies, and collaborative approaches are key to achieving effective and sustainable governance in this digital era. The future outlook discusses expected paradigm shifts, emphasizing the need for adaptable regulations and closer global collaboration to address new challenges. Looking ahead, this article proposes policy directions and governance practices that enable the world to harness the positive potential of digital transformation without neglecting responsibility to the global community.